Pericarditis Due to Campylobacter Fetus Subsp. Fetus: a Case Report of an Uncommon Infection - Fernandes, MA (2023)
Pericarditis is a common condition with numerous aetiologies. Bacteria other than the Mycobacterium tuberculosis complex are an exceptional cause. We present a case of subacute pericarditis highly probable due to Campylobacter fetus subsp. fetus in an immunosuppressed patient undergoing biologic therapy in relation to systemic lupus erythematosus (SLE). On admission, the patient presented with chest pain, dyspnea, and diaphoresis and has lately developed fever and a large pericardial effusion (PE) with a concomitant increase in the inflammatory parameters. The clinical presentation, along with the exclusion of a flare of the autoimmune disease and the isolation of Campylobacter fetus subsp. fetus on blood samples permitted the diagnosis. After therapy with antibiotics and colchicine, the patient showed full recovery.